Does calling alcoholism an illness make a difference? The public image of alcoholism in Italy. (1st September 2016) - Piras, Anna Paola; Preti, Antonio; Moro, Maria Francesca; Giua, Alice; Sini, Giulia; Piras, Martina; Pintus, Mirra; Pintus, Elisa; Manca, Annaraffaela; Cannas, Glenda; Cossu, Giulia; Angermeyer, Matthias Claus; et al.
Highlights: Links between stigma attached to alcoholism and its definition as illness were investigated. The definition of alcoholism as an illness is not related to a less negative stereotype. Unfavorable attributes were more likely to be ascribed to the alcoholic person than favorable ones. The public image of the 'alcoholic' was particularly dominated by associations with social deviance rather than with illness. Abstract: Aims: Using data from a population survey in two communities in the region of Sardinia, Italy, we examined the association between illness definition and attribution of personal characteristics to people with alcoholism. Methods: Quota samples, stratified by gender and age, were drawn from the general population (males: 48%; mean age 48 ± 18; range: 15–90). A fully-structured interview was conducted face-to-face with 404 respondents. The assessment of the public view of 'alcoholics' was measured by their reactions to stimulus words rated on bipolar scales, and defined with adjectives with opposite meanings at each end. Results: 322 participants (80%) rated the 'alcoholic' as 'ill'. The definition of the 'alcoholic' as being ill showed a statistically higher odd of stigma across all the dimensions of personal attributes. Conclusions: The expectation that people adopting the illness model would tend to blame less those afflicted for their condition and, consequently, stigmatize them less, was not confirmed.